Testing multisample compound symmetry (2003)
ABSTRACT: This paper is concerned with testing multisample compound symmetry of k multivariate Gaussian models. The likelihood ratio test statistic and its null moments for testing multisample compound symmetry have been derived. The asymptotic null distribution of the test statistic has been obtained using Box's method. This test can be viewed as an extension of Wilks' test for testing intraclass correlation structure of a covariance matrix.